Hidden Curriculum: Conceptual Review and Practice of Its Implementation in the Context of Education - Muhammad Nurhalim -; Ahsan Hasbullah (IKIP PGRI Bojonegoro, 2026)
This article aims to examine the concept, categories, and implementation of hidden curriculum in school education. This research uses library research, examining reputable literature in the form of journals, books, and previous research on educational values, norms, attitudes, and practices that are not written but affect the development of students. The results of the study show that hidden curriculum plays an important role in shaping students' character, professionalism, and social-emotional competence, as well as mediating the effectiveness of the formal curriculum. Hidden curriculum is categorized into structural, educational, cultural, and social factors, with positive practices such as teacher exemplarity, collaboration, and integrity rewards, as well as negative practices such as discrimination, excessive hierarchy, and inconsistent behavior. The optimization strategy includes learning environment management, teacher training, and monitoring of school socio-cultural interactions. The findings confirm the need for conscious management of the hidden curriculum to support holistic educational goals.